Extracorporeal Membrane Oxygenation for Septic Shock in Adults and Children: A Narrative Review - Broman, Lars Mikael; Dubrovskaja, Olga; Balik, Martin (Journal of clinical medicine, 2023)
Refractory septic shock is associated with a high risk of death. Circulatory support in the form of veno-arterial extracorporeal membrane oxygenation (VA ECMO) may function as a bridge to recovery, allowing for the treatment of the source of the sepsis. Whilst VA ECMO has been accepted as the means of hemodynamic support for children, in adults, single center observational studies show survival rates of only 70-90% for hypodynamic septic shock. The use of VA ECMO for circulatory support in hyperdynamic septic shock with preserved cardiac output or when applied late during cardio-pulmonary resuscitation is not recommended. With unresolving septic shock and a loss of ventriculo-arterial coupling, stress cardiomyopathy often develops. If the cardiac index (CI) approaches subnormal levels (CI < 2.5 L/min m-2) that do not match low systemic vascular resistance with a resulting loss of vital systemic perfusion pressure, VA ECMO support should be considered. A further decrease to the level of cardiogenic shock (CI < 1.8 L/min m-2) should be regarded as an indication for VA ECMO insertion. For patients who maintain a normal-to-high CI as part of their refractory vasoparalysis, VA ECMO support is justified in children and possibly in patients with a low body mass index. Extracorporeal support for septic shock should be limited to high-volume ECMO centers.
Keywords: distributive shock; septic shock; stress cardiomyopathy; refractory vasoparalysis; extracorporeal membrane oxygenation; cardiac output